Efektivitas Pelaksanaan Layanan Publik dengan Aplikasi E-Court di Pengadilan Negeri Lubuk Sikaping - Mela Saputri; Jumiati Jumiati (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2023)
This research purposes to reveal the Implementation of Public Services Effectiveness with the E-Court Application at the Lubuk Attitudeing District Court, to find out the obstacles in the Implementation of Public Services Effectiveness with the E-Court Application, and to find out the steps taken in overcoming the obstacles to the Implementation of Public Services Effectiveness with the E-Court Application. This research used method of descriptive qualitative. Based on the research result on the Implementation of Public Services with the E-Court Application at the Lubuk Attitudeing District Court it has not been effective, this is because there are several indicators of the eight indicators that have not been achieved properly. In the case of implementing public services Effectiveness with the E-Court application at the Lubuk Attitudeing District Court, there are still obstacles both internal and external, such as limited resources of human, inadequate facilities and infrastructure, and a public knowledge was lack. Steps taken in overcoming obstacles to the Implementation of Public Services with the E-Court Application are carried out by participating in training such as training, or technical guidance, and conducting outreach.